Comprehensive and comparative lipidome analysis of Vitis vinifera L. cv. Pinot Noir and Japanese indigenous V. vinifera L. cv. Koshu grape berries - Arita, Kayo (PLoS One, 2017)
Vitis vinifera cv. Koshu is an indigenous grape cultivar that has been cultivated for more than a thousand years in Japan and one of the most important cultivars in white winemaking. To improve Koshu wine quality, it is necessary to identify the metabolites in Koshu berry. We conducted a comprehensive and comparative lipidome analysis of Koshu and Pinot Noir berries cultivated in the same location in Japan using GC-MS/MS for fatty acids and LC-MS for glycerolipids and glycerophospholipids. Koshu skins and juices contained 22 and 19 fatty acids, respectively, whereas 23 and 20 fatty acids were detected in Pinot Noir skins and juices. C22:6n3 and C24:0 contents in Koshu skins were two and three times higher than those in Pinot Noir skins. C24:0 content in Koshu juices was also higher than that in Pinot Noir juices. Forty-nine lipid components (six digalactosyldiacylglycerols, one monogalactosyldiacylglycerol, 10 phosphatidylcholines, 12 phosphatidylethanolamines, and 20 triglycerides) were detected in Pinot Noir and Koshu skins. Strong peaks were observed for MGDG 36:6, DGDG 36:6, PC 34:2, PC 36:5, TG 54:6, TG 54:7, and TG 54:8 in Koshu skins. The contents of 36 of the 49 lipid components were significantly higher in Pinot Noir skins than Koshu skins. Pinot Noir skins contained more lipids whose alkyl chains have more than 18 carbons than Koshu skins. Further analysis of both lipid profiles revealed that the number of double bonds in a fatty acid molecule in Pinot Noir skins and juices was significantly larger than that in Koshu skins and juices. A strong relationship exists between the heat requirement of grapevine cultivars and the level of fatty acid desaturation. C18-fatty acids were the major components in Koshu and Pinot Noir berries. The expression levels of C18-fatty acid desaturases regulated the accumulation of C18-unsaturated fatty acids in berry skins. The loss of C18:3 in Koshu berries at the end of ripening was observed. Koshu might effectively convert C18:3 into (Z)-hex-3-enal for the production of C6-aroma compounds. These findings by the lipidome analysis are expected to contribute to the improvement of Koshu wine aroma and breeding strategies of cold-tolerant Koshu grapevines.